RE-SCHEDULING OF THE CRUDE OIL STORAGE TANK MSTB T-701D PROJECT USING THE CRITICAL PATH METHOD (CPM) AND CRITICAL CHAIN PROJECT MANAGEMENT (CCPM) - Dinda Syafa Rachmanur Firdaus; Farida Pulansari (Center for Study and Journal Management FTI UMI, 2023)
In the MSTB T-701D Crude Oil Storage Tank project, good scheduling is needed so that the project can run smoothly during the process. The most frequently used methods in designing project scheduling are the Critical Path Method and the Critical Chain Project Management. This study aims to compare scheduling results between the traditional CPM and the CCPM methods. The project used in this research analysis is the Crude Oil Storage Tank MSTB T-701D project. The Root Square Error Method (RSEM) is used to find the buffer size. In the scheduling analysis, calculations are carried out manually and with the help of Primavera P6 software as validation for calculating the total float, critical path, and project network. Project scheduling using the Critical Path Method (CPM) is known to be completed in 164 days. Whereas for the CCPM, the project can be completed in 140.1 days plus the RSEM buffer calculation method of 5.29 days, and the total scheduling with CCPM produces 145.3 days. This analysis shows that the traditional CPM method has a larger estimated duration than CCPM with an RSEM sizing buffer. Then a suggestion was made to work on the MSTB T-701D Crude Oil Storage Tank project using the CCPM and RCA methods.